Palladium-catalyzed asymmetric synthesis of 2-alkynyl oxacycles. - Daniels, D; Thompson, A; Anderson, E (2011)
Oxyacetylene: Unusual palladium-catalyzed cyclizations of cyclic and acyclic propargylic carbonates give 2-alkynyl oxacycles. The reactions proceed with very high stereoselectivity for both syn- and anti-disubstituted furans and pyrans, and with exceptional regioselectivity. In addition, two-directional cyclizations of bis-propargylic carbonate substrates yield bifurans with complete stereocontrol for all diastereomers. © 2011 WILEY-VCH Verlag GmbH and Co. KGaA, Weinheim.